(untitled) (Global Journal of Human-Social Science, 2025)
This study assesses the effectiveness of the Unrepresented Nations and Peoples Organization s UNPO advocacy e fforts o n b ehalf o f t he U yghur c ommunity i n E ast Turkestan Xinjiang C hina T he U NPO a long w ith o ther organizations has sought to raise awareness of human rights abuses - including mass detention forced labor and cultural repression of marginalized communities such as the Uyghurs - and t o i nfluence p olicy i n s upport o f t his c ause U sing quantitative survey data from 416 participants comprising UNPO staff and Uyghur activists this research evaluates the perceived effectiveness of UNPO s transnational advocacy strategies across key areas global awareness-raising political representation policy influence and collaboration with other organizations The results indicate that while UNPO s efforts to raise awareness of human rights violations affecting marginalized communities are acknowledged particularly through media and public relations activities its ability to drive substantial policy changes or international legal actions remains limited Significant discrepancies were observed between the perceptions of UNPO staff who rated their advocacy efforts positively and Uyghur activists who expressed more critical views on the organization s overall impact These differences point to a gap between the organization s strategic objectives in advocacy effectiveness and the practical outcomes experienced by the Uyghur community T he s tudy c oncludes t hat d espite s ome achievements UNPO faces challenges in converting advocacy into meaningful political and legal reforms particularly in the face of opposition from powerful states like China Recommendations for improvement include stronger collaboration with other organizations a greater focus on policy and legal advocacy and more alignment with the needs of marginalized communities